Stomach Content Analysis of Osprhonemus gouramy Lac From the Pinang Luar Oxbow Lake, Buluhcina Village, Kampar Regency, Riau Province - Aina, Nurul; Efizon, Deni; ', Efawani (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
Osphronemus gouramy Lac is one of freshwater fish that inhabit the Pinang Luar Lake. This fish is the most common fish in the lake, but information on its stomach content is rare. A research aims to understand the stomach content had been conducted from March-April 2017. Sampling was conducted once/ week for a one month period. There were 67 fishes captured. Stomach contents were analyzed as a basis for calculating the Preponderance Index (PI). The analysis was conducted using the gravimetric method. Results shown that in all fish captured, the content of the stomach consists of aquatic plant stem, leaves, fish scales and insect remains (shell and legs). The main food of O. gouramy is plant materials (94%). Based on the data obtained, this fish can be categorized as herbivore.Keyword : Gravimetric, Herbivore, Osphronemus gouramy, Oxbow Lake